Living with osteoarthritis: a systematic review and meta-ethnography. (November 2014) - Smith, TO; Purdy, R; Lister, S; Salter, C; Fleetcroft, R; Conaghan, P
<x xml:space="preserve">Abstract</x> Objectives: To review and synthesize the existing literature on the experience of living with a diagnosis of hip and/or knee osteoarthritis (OA). Method: A systematic review was undertaken using meta-ethnography. A search of both published (AMED, CINAHL, EMBASE, PsychINFO, SportsDisc, MEDLINE, Cochrane Clinical Trials Registry, PubMed) and unpublished/trial registry databases [World Health Organization (WHO) International Clinical Trials Registry Platform, Current Controlled Trials, the United States National Institute of Health Trials Registry, National Institute for Health Research (NIHR) Clinical Research Portfolio Database] was undertaken from their inception to 5 June 2013. Results: Thirty-two studies formed the meta-ethnography of the lived experiences of people with OA. In total, 1643 people with OA were sampled, the majority diagnosed with knee OA. The evidence base was weak to moderate in quality. The majority of studies indicated that people viewed living with OA negatively. Four key factors influenced their attitudes to the condition: the severity of their symptoms; the impact of these symptoms on their functional capability; their attitude towards understanding their disease; and their perceptions of other people's beliefs towards their disease. Conclusions: The current literature suggests that greater knowledge of the pathology of OA, management of symptoms, promotion of functional activity for patients and their family/friends networks, and understanding to better inform OA patient's role in society are all important elements that affect a person's attitude to OA. By better understanding these factors during future consultations, clinicians may forge stronger relationships with their patients to more effectively manage this long-term disabling condition.